AGRONOMIC PERFORMANCE OF COWPEA CULTIVARS DEPENDING ON SOWING SEASONS IN THE CERRADO BIOME - Almeida, Fernando da Silva (2017)
The objective of this work was to assess the agronomic performance of cowpea cultivars depending on sowing seasons in the Cerrado biome. Thus, an experiment was conducted in Uberaba, State of Minas Gerais, Brazil, in a complete randomized block design, in a 6x3 factorial arrangement, using six cowpea cultivars (BRS-Itaim, BRS-Guariba, BRS-Potengi, BRS-Cauamé, BRS-Novaera and BRS-Tumucumaque) and three sowing seasons (Dec 14, 2012; Jan 14, 2013; and Feb 14, 2013), with four replications. The interaction between the cultivars and sowing seasons was assessed regarding the number of days for full flowering, number of days for pod maturation, number of trifoliate leaves, height of the first pod-bearing node, pod length, number of pods per plant, final plant population, 100-grain weight and grain yield. The cowpea cultivars sown in December produced the lowest numbers of pods per plant and grains per pod, resulting in the lowest grain yields. The cultivar BRS-Tumucumaque had the highest grain yield in the January sowing. The highest grain yields were found in the February sowing, especially when the cultivars BRS-Itaim (3,439 kg ha-1), BRS-Novaera (3,435 kg ha-1), BRS-Guariba (3,168 kg ha-1) and BRS-Potengi (3,107 kg ha-1) was used.